2020
DOI: 10.1016/j.cmi.2019.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of antibody and memory T-cell response in H7N9 survivors: a cross-sectional analysis

Abstract: Objectives: Despite the importance of immunological memory for protective immunity against viral infection, whether H7N9-specific antibodies and memory T-cell responses remain detectable years after the original infection is unknown. Methods: A cross-sectional study was conducted to investigate the immune memory responses of H7N9 patients who contracted the disease and survived during the 2013e2016 epidemics in China. Sustainability of antibodies and T-cell memory to H7N9 virus were examined. Healthy individua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…In a cohort of H7N9 survivors who were followed up for 15 months after infection, although the H7N9-specific antibody concentrations declined over time, the frequency of virus-specific IFN-g-secreting T cells increased within 1 year of infection [89]. This phenomenon was confirmed in another cross-sectional study involving survivors at 36 months after infection [90]. This increasing trend over time within 1 year of infection was more obvious in patients aged ≥ 60 years and in critically ill patients requiring ventilation during their infections.…”
Section: Cell-mediated Immunity In Convalescencementioning
confidence: 71%
“…In a cohort of H7N9 survivors who were followed up for 15 months after infection, although the H7N9-specific antibody concentrations declined over time, the frequency of virus-specific IFN-g-secreting T cells increased within 1 year of infection [89]. This phenomenon was confirmed in another cross-sectional study involving survivors at 36 months after infection [90]. This increasing trend over time within 1 year of infection was more obvious in patients aged ≥ 60 years and in critically ill patients requiring ventilation during their infections.…”
Section: Cell-mediated Immunity In Convalescencementioning
confidence: 71%
“…Serology studies have shown that human H7N9 virus infection stimulates the induction of H7-reactive antibody responses that persist for at least several years ( 10 , 11 , 24 , 38 ). Kinetic monitoring of such responses revealed that heterosubtypic H7 and H3 binding/neutralizing antibody responses typically appear and peak earlier than H7 subtype responses, likely mediated by memory recall of H3-reactive clones ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…In another cross-sectional study, Ma et al reported that HAI GMT was near 40 at about 26 months after illness onset, which was similar to our findings. 21 For the pooled analyses of antibody kinetics, data for antigens that were antigenically-matched to circulating strains are preferred. However, there might be antigen-specific differences in HAI titers, which could affect the results.…”
Section: Discussionmentioning
confidence: 99%
“…37 For A(H7N9) virus-specific antibody responses after discharge in survivors, Ma et al found no association between disease severity and antibody response in one study, 20 while reported that severe disease was associated with higher HAI titer after discharge in another study. 21 Antibody responses to A(H5N1) virus infection after recovery have been reported to be lower in patients with asymptomatic infection than in those with severe illness. 30 Previous studies in A(H7N9) virus infected patients indicate that effective cross-reactive T cell memory is important for protection against severe influenza disease caused by newly emerging influenza A viruses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation